A reliable technique to quantify the individual variability of iridescent coloration in birds. (14th November 2015) - Van Wijk, Sonia; Bélisle, Marc; Garant, Dany; Pelletier, Fanie
Abstract : The study of iridescent coloration in birds emerged only recently, mainly due to the difficulty inherent in quantifying its directionality. Directionality restrains color perception to a limited angle and thereby causes drastic changes in brightness when an animal is in motion. Although a versatile goniometer for quantifying iridescent coloration has been developed recently, so far, it has only been applied to measuring the highly directional iridescent coloration in a hummingbird species. Thus, the reliability of the goniometer for species displaying more common and less directional iridescent coloration has yet to be evaluated. Additionally, two important methodological aspects remain to be assessed before this apparatus can be used confidently: 1) whether directionality, which could be subject to sexual selection, can be quantified in a repeatable way; and 2) whether the apparatus gives more precise and accurate measurements than a less complex traditional method. Using feathers collected from 271 male tree swallows Tachycineta bicolor over two years, we found that the goniometer provided repeatable measurements of directionality across individuals and across three body regions, namely the crown, mantle and rump. The apparatus was also more repeatable than a traditional method involving a bifurcated probe and reduced a brightness bias associated with individual differences in barbule tilt. We strongly encourage researchers to invest in this methodological change considering the multiple advantages demonstrated and to quantify the directionality of iridescent coloration as to unveil its role in signaling and sexual selection.